Efficacy of non-surgical treatments for androgenetic alopecia in men and women: a systematic review with network meta-analyses, and an assessment of evidence quality. (2nd January 2022) - Gupta, Aditya K.; Bamimore, Mary A.; Foley, Kelly A.
Abstract: Background and objective: Various treatments exist for androgenetic alopecia (AGA); we determined the relative efficacies of non-surgical AGA monotherapies separately for men and women. Methods: Randomized controlled trials (RCTs) were systematically searched in PubMed, EMBASE, Scopus and clinicaltrials.gov. Separate networks were used for men and women; for each network, a Bayesian network meta-analysis (NMA) of mean change in hair count from baseline (in units of hairs per square centimeter) was performed using a random effects model. Results: The networks for male and female AGA included 30 and 10 RCTs, respectively. We identified the following treatments for male AGA in decreasing rank of efficacy: platelet-rich plasma (PRP), low-level laser therapy (LLLT), 0.5 mg dutasteride, 1 mg finasteride, 5% minoxidil, 2% minoxidil, and bimatoprost. For female AGA the following were identified in decreasing rank of efficacy: LLLT, 5% minoxidil, and 2% minoxidil. The evidence quality of the highest ranked therapies, for male and female AGA, was judged to be low. Conclusions: While newer treatments like LLLT may be more efficacious than more traditional therapies like 5% minoxidil, the efficacy of the more recent treatment modalities needs to be further validated by future RCTs.